ESTIMATED AVERAGE TIME TO HIRE EMPLOYEES OF THE COMPANY BASED ON KUMARASWAMY DISTRIBUTION - Usraini, Laisa (Operations Research: International Conference Series, 2023)
Recruitment of employees in a company is a process starting from selecting and receiving prospective employees, in order to find workers who are able to work in a company. However, companies must know when recruitment will open. The purpose of this research is to find out how long the average opportunity time of recruitment is. The method used is the Kumaraswamy distribution with three parameters as benchmarks for the estimated recruitment time, in order to find out how long the chances of the recruitment lasting using a simplified survival function using the properties of the Laplace transform. Based on the estimation of the average time of recruitment, the results show that the greater the value of the parameters the less chance the average recruitment time is or the tighter the prospective employees are accepted.